1997
DOI: 10.1046/j.1471-4159.1997.68041655.x
|View full text |Cite
|
Sign up to set email alerts
|

Up‐Regulation of Sodium Channel Subunit mRNAs and Their Cell Surface Expression by Antiepileptic Valproic Acid: Activation of Calcium Channel and Catecholamine Secretion in Adrenal Chromaffin Cells

Abstract: Treatment of cultured bovine adrenal chromaffin cells with a therapeutic concentration (0.6 mM) of valproic acid (VPA) for >24 h caused a time-dependent (t 112 = 74 h) increase in [ 3H]saxitoxinbinding up to 1.4fold without altering the KD value; it was prevented by the simultaneous treatment with cycloheximide (an inhibitor of protein synthesis). VPA also raised Na~channel aand /3 1-subunit mRNA levels 1.4-and 1.7-fold at 24 h, and 1 .6-and 1.8-fold at 72 h, respectively. Chronic (but not acute) exposure to V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 45 publications
8
57
0
Order By: Relevance
“…Each of the three transcripts had a high level of hybridization to the Affymetrix mismatch probes, providing an explanation for why MAS5 did not pick up the change. Interestingly, VPA has been shown to modulate sodium channel-␤1, and this is likely associated with its pharmacological mechanism of action (51). The increase in lanosterol-14-demethylase transcript after VPA treatment has not been reported previously.…”
Section: Discussionmentioning
confidence: 92%
“…Each of the three transcripts had a high level of hybridization to the Affymetrix mismatch probes, providing an explanation for why MAS5 did not pick up the change. Interestingly, VPA has been shown to modulate sodium channel-␤1, and this is likely associated with its pharmacological mechanism of action (51). The increase in lanosterol-14-demethylase transcript after VPA treatment has not been reported previously.…”
Section: Discussionmentioning
confidence: 92%
“…VPA increases GABA levels and augments signaling through this pathway by altering GABA metabolic pathways and influencing GABA receptor activity (25,67,69). VPA impinges on several other molecular and cellular processes, such as the activity and expression of ionic channels, Wnt signaling, and Akt regulation (6,17,19,27,67,92,99). Activation of the extracellular signal-regulated kinase (ERK) pathway is commonly observed following VPA treatment (67,104).…”
Section: Discussionmentioning
confidence: 99%
“…22 Na ϩ influx was measured by incubating the cells with 2 Ci 22 NaCl at 37°C for 5 min in 1 ml of KRP buffer in the absence or presence of veratridine, ouabain, PbTx-3, and nicotine. The cells were washed with ice-cold KRP buffer, solubilized in 10% Triton X-100, and counted for radioactivity (Wada et al, 1986(Wada et al, , 1992Yamamoto et al, 1996Yamamoto et al, , 1997Yanagita et al, 1996;Yuhi et al, 1996;Shiraishi et al, 2001a,b).…”
Section: Methodsmentioning
confidence: 99%
“…In adrenal chromaffin cells, our previous studies showed that nicotinic receptor agonists rapidly increase 22 Na ϩ influx within 1 min, which passes through nicotinic receptor-associated cation channels (but not through voltage-dependent Na ϩ channels) and gates voltage-dependent Ca 2ϩ channels (Wada et al, 1986;Yamamoto et al, 1997). In the present study, we examined whether treatment of adrenal chromaffin cells with serum deprivation, 50 M PD98059 or 10 M U0126 for 24 h could alter the activity of nicotinic receptorassociated cation channels.…”
Section: Erk: Constitutive Down-regulation Of Namentioning
confidence: 99%